EFEK PENAMBAHAN POLY LACTIC CO GLYCOLIC ACID TERHADAP POROSITAS SCAFFOLD HIDROKSIAPATIT NANOPARTIKEL – POLIVINYL ALKOHOL SEBAGAI KANDIDAT MATERIAL BONEGRAFT - Feni Istikharoh; Lalita El Milla; Ericka Fairuz Ramadhani (E-Prodenta Journal of Dentistry, 2023)
Background: Bone loss has a major impact on the process of placing implants and dentures. Nanoparticle hydroxyapatite (HANP) has better biodegradability and mechanical properties than micro-particle hydroxyapatite. PVA is a synthetic polymer that is cheap, hydrophilic, has high mechanical stability and flexibility but low biodegradability. PLGA is a new synthetic polymer which is widely used in the biomedical, however PLGA has less osteoconductive properties. The ideal scaffold has several important characteristics, one of which is having a porosity of>70%.  Objective: To know the role of PLGA on the porosity of the scaffold by comparing the porosity of the HANP-PVA scaffold and the HANP-PVA scaffold given PLGA Methods: Group 1 was the HANP-PVA scaffold with a content of 20% HANP (w / w). Group 2 was the HANP-PVA scaffold which added 20% (w/w) of PLGA. Both groups were synthesized by freeze drying method at -80oC for 24 hours. The porosity test was used the liquid displacement method for 24 hours. Statistical testing using Shapiro Wilk, Levene's test and Independent t-Test Results: The porosity of the HANP-PVA scaffold was 77.90% ± 4.51 and the HANP-PVA-PLGA scaffold was 87.55% ± 5.67. The Shapiro-Wilk normality test showed that the data were normally distributed (p> 0.05). The independent t test showed a significant difference between the HANP-PVA and HANP-PVA-PLGA scaffold (p <0.05) Conclusions: The addition of PLGA to the scaffold can increase the porosity of the HANP-PVA scaffold. HANP-PVA-PLGA has the potential to accelerate bone regeneration after extraction  Keyword: bone loss, PVA, PLGA, Hydroxyapatite nanoparticle